Implementasi Internet dalam Rangka Peningkatan Kunjungan Pengguna Perpustakaan Daerah Kabupaten Badung - Bakti, Dewi; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT The title of this study, is the of internet the type of this research is quantitative descriptive research which is aimed to. Examine the us of the internet in the Public Library of Badung Regency Bali and the effect of the implementation of the internet in the Library. The expected benefits of this research are for educational institution and for the Library itself The study is located in the Public Library of Badung Regency. The population in this study is all visitors in the Public Library of Badung Regency and the sample is among of the population  technique used is in the research Random Sampling. The data collection techniques used is this study are observation and purposive questionnaires, but the analysis technique is a simple linear regression analysis which using the formula Y = a + bX Keywords: Internet, Library, Research